Operational characteristics of somatostatin receptors mediating inhibitory actions on rat locus coeruleus neurones. - Chessell, I. P. (1996)
1. In order to characterize somatostatin (SRIF) receptor inhibiting spontaneous firing of rat locus coeruleus neurones, and their transduction mechanism(S), extracellular recordings were obtained from a pontine slice preparation of rat brain containing the locus coeruleus (LC). LC neurones were identified by electrophysiological and pharmacological properties; spontaneous firing (characteristically 0.5-5 Hz) was reversibly and concentration-dependently inhibited by exogenously applied noradrenaline. 2. Spontaneous firing of LC neurones was reversibly and concentration-dependently inhibited by SRIF and the N-terminally extended form, somatostatin-28 (SRIF-28), with EC50 values of 15.1 and 19.4 nM, respectively. The synthetic SRIF analogues (octreotide, MK-678, BIM-23027 and L-362,855) also caused concentration-dependent inhibition of LC neurone firing with a rank order of agonist potencies compatible with actions at a receptor resembling the recombinant sst2 receptor. The putative sst3 selective agonist, BIM-23056, was without agonist or antagonist effect. 3. Addition of 100 nM desipramine significantly increased the efficacy of exogenously applied noradrenaline (EC50 values, 2.96 and 0.13 microM, absence and presence of desipramine, respectively) but did not significantly affect SRIF-induced inhibition (EC50 values, 15.6 and 8.0 nM, respectively). Furthermore, application of phenoxybenzamine (3 microM) abolished responses to NA, but did not affect responses to SRIF (EC50 = 14.1 nM). 4. Application of the cyclic AMP analogue, 8-bromoadenosine-cyclic monophosphate (8-Br-cyclic AMP; 500 microM), significantly increased the spontaneous firing rate of all neurones tested (223 +/- 24% over basal rate). Concentration-effect curves for SRIF constructed in the absence and presence of 8-Br-cyclic AMP had similar threshold concentrations, maxima and EC50 values. 5. Incubation of pontine slices in a modified artificial CSF containing 500 ng ml-1 pertussis toxin (PTX) for 18 h prior to extracellular recording affected neither the spontaneous firing of LC neurones, nor the inhibitory responses to muscimol (EC50 2.2 and 1.2 microM, absence and presence of PTX). However, inhibitory responses to SRIF were markedly attenuated. 6. We conclude that the inhibitory actions of SRIF on spontaneous firing of LC neurones are mediated directly by activation of somatodendritic SRIF receptors, and not indirectly by release of noradrenaline. The SRIF receptors involved appear to couple via a pertussis toxin sensitive G-protein, and elicit their response by a mechanism apparently independent of inhibition of cyclic AMP formation. The agonist profile of several selective and novel SRIF analogues suggests the identity of this receptor to be similar to the recombinant sst2 receptor.